AN ANALYSIS ON GRAMMATICAL ERRORS OF STUDENTS’ WRITINGS - Qurinta Shinta (Bajang Institute, 2021)
The purpose of this descriptive study is to examine students' grammatical errors in their writings at Diponegoro University's First Semester Public Health Students. The target population consisted of 20 Public Health students of UNDIP enrolled in an English class who were chosen at random from a pool of 75. A writing assignment was conducted to asses the students grammatical errors based on surface strategy taxonomy. The results show the errors form the highest to the lowest percentage: misinformation (56,8%), omission (23,5%), addition (19,6%) and misordering (0%). Based on the results, it can be concluded that misinformation especially dealing with alternating forms is the most frequent errors made by students. This is caused by poor understanding of grammatical structure, lack of vocabulary mastery, and L1 direct translation tendencies